An Experimental Study and Analysis on Solar Drying of Bitter Gourd Using an Evacuated Tube Air Collector in Thanjavur, Tamil Nadu, India. (23rd May 2013) - Umayal Sundari, AR.; Neelamegam, P.; Subramanian, C. V.
Abstract : The objective of this research work is to design and develop a forced convection solar dryer using evacuated tube air collector and study its performance on bitter gourd in Thanjavur District, Tamilnadu, India. The designed solar dryer consists of a drying chamber, evacuated tube air collector, a blower, and a chimney. Drying parameters, moisture ratio and drying rates, are calculated and their performance is compared with natural sun drying. The results of the present study show that the proposed solar dryer has greater efficiency, and the moisture content of bitter gourd is reduced from 91% to 6.25% in 6 hours as compared to 10 hours in natural sun drying. In this solar dryer, the products are uniformly dried, and the moisture content of the sample is controlled. It is found that the quality of the dried bitter gourd using solar dryer is higher than the natural sun-dried bitter gourd.